UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA LUNTAR DENGAN MODEL PBL PEMBELA GALA DI KELAS V SD N ORO ORO OMBO TAHUN 2023/2024 - Riska ayu tri lestari; Novi Ayuningtias Widianti; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted with the aim of measuring improvements in Mathematics learning outcomes regarding the area of ​​flat shapes using the Problem Based Learning (PBL) learning model which applies differentiated learning according to the learning styles of V students at the Oro Oro Ombo State Elementary School in 2023/2024. The subject of this research There are 19 students in class V of the Oro Oro Ombo State Elementary School, with 7 female students and 12 male students. This research was conducted because class V students at SD Negeri Oro Oro Ombo Madiun City had not yet reached the predetermined learning achievement indicators. To overcome this problem, learning improvements were carried out using the Classroom Action Research (PTK) method with two cycle stages. Increasing student learning outcomes in the area of ​​flat shapes learning material is not the same as using the Problem Based Learning (PBL) learning model which applies differentiated learning according to the students' learning styles in each cycle. This can be seen from the average value of student learning outcomes in cycle 1 is 70, with a completion percentage of 42,11%. In cycle 2, there was an increase in the average learning outcome score to 79, with a completion percentage reaching 78.95%. The results of this research show that the Problem Based Learning (PBL) learning model which applies differentiated learning according to students' learning styles has a significant increase in mathematics learning outcomes for the area of ​​plane figures in class V.